Nitrogen Dynamics in Wetland Systems and Its Impact on Biodiversity - Anum Yousaf; Noreen Khalid; Muhammad Aqeel; Ali Noman; Nayab Naeem; Wajiha Sarfraz; Ujala Ejaz; Zonaira Qaiser; Arifa Khalid (Nitrogen, 2021)
Wetlands are viable sinks for nitrate and have also been identified as a source of nitrous oxide, a product of two microbially regulated processes: nitrification and denitrification. Anthropogenic expansion of nitrogen is a leading cause of the eutrophication of water bodies and may also contribute to the deterioration of the ozone layer in the stratosphere. Wetlands ameliorate the quality of water percolating through them, by retaining nutrients and sequestering carbon, and simultaneously enhancing the flora and fauna diversity of these landscapes. Among the many services these wetlands provide, they also alleviate nitrate pollution by attenuating reactive nitrogen from agricultural drainage and ensure the effective reclamation of the wastewater. The literature regarding the viability of wetlands suggests a linear relationship between the removal of nitrogen and its loading rate, thereby suggesting a potential loss of nitrogen removal capacity due to the loss of wetland area. This review discusses the nitrogen removal mechanisms in existing wetlands along with the environmental variables affecting the optimum performance and management of these wetlands, in terms of greenhouse gas retention and biodiversity. Conservation of these wetlands should be contemplated to maintain the world-wide nitrogen cycle and diminish the negative repercussions of surplus nitrogen loading.